2019
DOI: 10.1177/1078155219837342
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab-induced hepatitis: A rare side effect of an immune check point inhibitor

Abstract: Immune checkpoint inhibitors have ushered in a new era in cancer management. Nivolumab is a human immunoglobulin G4 (IgG4) monoclonal antibody that selectively inhibits programmed cell death-1 (PD-1) activity by binding to the PD-1 receptor. This inhibits suppression of the T-cell activity, which can in turn cause increased killing of cancer cells. This alteration in the activity of the T cells can cause them to lose their ability to identify host cells and leads to immune-related adverse effects (irAE). Nivol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
(20 reference statements)
0
9
0
1
Order By: Relevance
“…To our knowledge, this is the first documented report of a patient developing acute liver failure shortly after ICI initiation. A single case of nivolumab-induced hepatitis in a patient with renal cell carcinoma which developed within two weeks of therapy initiation was previously reported but was not as clinically severe [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first documented report of a patient developing acute liver failure shortly after ICI initiation. A single case of nivolumab-induced hepatitis in a patient with renal cell carcinoma which developed within two weeks of therapy initiation was previously reported but was not as clinically severe [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,3 However, this alteration in the activity of the T-cells can cause them to lose their ability to identify host cells and lead to immune-related adverse events, including dermatitis, thyroid dysfunction, hepatitis, pneumonitis, hypophysitis, enteritis, nephritis, and rarely, hematologic effects. 3,4…”
Section: Discussionmentioning
confidence: 99%
“…Nivolumab is a PD-1 ICI antibody that disrupts the interaction of the PD-1 receptor with its ligands PDL-1 and PDL-2, thereby enhancing antitumor immunity, delaying tumor progression, and facilitating tumor rejection. 1,3 However, this alteration in the activity of the T-cells can cause them to lose their ability to identify host cells and lead to immune-related adverse events, including dermatitis, thyroid dysfunction, hepatitis, pneumonitis, hypophysitis, enteritis, nephritis, and rarely, hematologic effects. 3,4 The cytokine interleukin-2 (IL-2) is an essential growth factor for T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…The management strategy for this side effect was administration of steroids and the patient began to exhibit improvements in liver function. However, she later developed substantial upper gastrointestinal bleeding secondary to a gastroduodenal ulcer and then developed acute tubular necrosis, ultimately succumbing to the complications ( 59 ). Lankes et al ( 60 ) reported severe diarrhea with ≤18 watery bowel movements per day in a patient with metastatic melanoma treated with ipilimumab.…”
Section: Digestive Systemmentioning
confidence: 99%